B309 Comparison of anterior, posterior and lateral approaches of ultrasound guided quadratus lumborum block in inguinal hernia surgery: a randomized controlled trial. (11th August 2022) - Kumar, A; Sinha, C; Kumar, A; Kumari, P; Kumar, K
Abstract : Background and Aims: Pain after inguinal hernia surgeries can lead to significant post-operative complications. Aim of this study was to compare the post-operative analgesic effect between USG guided trans-muscular, posterior and lateral approaches of the quadratus lumborum block in adult patients undergoing unilateral hernia surgery. Methods: Sixty ASA I/II adult patients scheduled for unilateral inguinal hernia surgery were recruited. Group I: Trans-muscular approach Group II: Lateral approach Group III: Posterior approach Subarachnoid block was given with 18 mg of 0.5% heavy bupivacaine in all patients. USG guided QL block was given by experienced anesthesiologist once the surgery was completed. Pain was assessed with a Numerical rating scale (NRS) at rest and with movement. Results: There were significant differences in the median NRS scores (p <0.001), worst NRS scores (p<0.001) and median dynamic NRS scores (p<0.001) between transmuscular, anterior and posterior approaches of the quadratus lumborum block. Postoperative analgesia requirement was highest in the anterior approach (180 μg [120, 200]) followed by posterior approach (140 μg [120, 160]) and was least in transmuscular approach (100 μg [100, 100]). A significant difference (p <0.001) was observed in the time required for rescue analgesia between transmuscular, anterior and posterior approaches of the quadratus lumborum block. Postoperatively, earliest requirement of analgesia was found in the anterior approach (8 hours [8, 9]) followed by posterior approach (10 hours [10, 12]). In transmuscular approach, analgesia was required postoperatively after 13 hours [12, 14], postoperatively Conclusions: Transmuscular QL block is better in providing postoperative analgesia in adult patients undergoing inguinal hernia surgeries.